2009
DOI: 10.1177/0306624x09344840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individual and Group Cognitive-Behavioral Therapy for Male Prisoners in Iran

Abstract: This study investigates individual and group cognitive-behavioral interventions in decreasing psychological symptoms and enhancing the psychological status of Iranian prison inmates. A random sample of 180 males is placed in three equal groups: an individual cognitive-behavioral therapy (CBT) group, an individual and group CBT group, and a control group. General Health Questionnaire, Symptom Checklist-90- Revised, and diagnostic interviews based on the Diagnostic and Statistical Manual of Mental Disorders (4th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
1
15
0
3
Order By: Relevance
“…However, non-significant group differences with respect to BDI-II and ATQ scores were observed, which is consistent with the study of Khodayarifard, Shokoohi-Yekta and Hamot (2010) demonstrated that both ICBT and GCBT were equally effective in reducing the depression symptoms.…”
Section: Effectiveness Of Interventions (Pre-intervention To Post-intsupporting
confidence: 88%
“…However, non-significant group differences with respect to BDI-II and ATQ scores were observed, which is consistent with the study of Khodayarifard, Shokoohi-Yekta and Hamot (2010) demonstrated that both ICBT and GCBT were equally effective in reducing the depression symptoms.…”
Section: Effectiveness Of Interventions (Pre-intervention To Post-intsupporting
confidence: 88%
“…"I have to be apprehensive about being on parole because that is what will keep me functional," she said. Taking a broad view the ability of practising and utilizing it in various situations helps reduce tension and impulsiveness throughout life (Khodayarifard & Shokoohi-Yekta, 2010). The outcome of the therapy received by the inmates involved in this study support appropriate decision-making, which eventually lead to evasion of criminal behaviour.…”
Section: Discussionmentioning
confidence: 70%
“…Through replacing the unfavourable patterns with adaptive cognitive and behavioural ones, these interventions enable the individual to make use of a richer behavioural range in dealing with their issues and to plan their actions (Khodayarifard & Shokoohi-Yekta, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Group therapy or group counseling for youth offenders in child prison is one of the best methods to build peer support. Research in many prisons has been implemented by using group psychotherapy and proved that combined therapy (group and individual) is stronger than individual only [7]. Group gave them more attention to fulfilling the psychological needs of youth prisoners and gave them 'opportunities' to experiment and feel that they were being understood by the groups [8].…”
Section: Analysis Of the Youth Offender Exposed To Group Counselingmentioning
confidence: 99%